Demography, Urbanization and Development : Rural Push, Urban Pull and... Urban Push? - Jedwab, Remi; Christiaensen, Luc; Gindelsky, Marina (Elsevier, 2018)
Developing countries have urbanized rapidly since 1950. To explain urbanization, standard models emphasize rural–urban migration, focusing on rural push factors (agricultural modernization and rural poverty) and urban pull factors (industrialization and urban-biased policies). Using new historical data on urban birth and death rates for 7 countries from Industrial Europe (1800–1910) and 35 developing countries (1960–2010), we argue that a non-negligible part of developing countries’ rapid urban growth and urbanization may also be linked to demographic factors, i.e. rapid internal urban population growth, or an urban push. High urban natural increase in today’s developing countries follows from lower urban mortality, relative to Industrial Europe, where higher urban deaths offset urban births. This compounds the effects of migration and displays strong associations with urban congestion, providing additional insight into the phenomenon of urbanization without growth.